ENOTOURISM AND SUSTAINABLE TOURISM IN POLAND - Cichy, Andrzej; Ochoa Siguencia, Luis; Marzano, Gilberto (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This paper presents a research conducted in three Polish regions, Dolny Slask, Malopolska, and Pod Karpacie, within the EU funded project “Innovation and Capacity Building in Higher Education for Cultural Management, Hospitality and Sustainable Tourism in European Cultural Routes” that aims to provide profitable solutions for sustainable tourism problems and focuses on how developing enotourism in places that have to improve their tourism capacity building. Based on literature analysis and the study of key cases, this article presents the reasons why enotourism is an important tourism opportunity in Poland. Our research was grounded on a cost and profit analysis of the enoutourism business and we considered a few of relevant cases of wine tourism experiences. Indeed, the principal aim of our research was to find innovative successfully ideas for this form of tourism. From our research, emerged that the most important factors for enhancing enotourism are incentivising laws, an effective cooperation between vineyard owners and tourist operators (e.g. hotels, restaurants, travel agencies, etc.) as well as the integration of enotourim with other local attractions.